Kerekayasaan Informasi Dalam Proses Bisnis - Diana Effendi (ULTIMA InfoSys, 2016)
Business process is a series of steps or actions to achieve a certain goal. It can be completed not only in parallel but also separately, by a person or a system. both inside and outside the organization. An enterprise needs an accurate, relevant, and just-in-time information to be operated well. That’s why information engineering is needed. Information engineering is an application of a set of related formal techniques for planning, analysis, design, and information system construction in the whole enterprise. This paper aims to summarize this idea comprehensively according to literature review. Index Terms - information engineering, business process, enterprise information system.